Severity and Clinical Outcome of COVID-19 Patients Admitted at a Provincial Infectious and Communicable Disease Hospital of Nepal: A Cross-Sectional Study - Gauchan, Bikash; Maskey, Aleena; Bhandari, Bishnu; Tiwari, Ashok; Sharma, Binod Bindu; Tiwari, Shreeram; Khadka, Khim Bahadur; Paudel, Subash; Kandel, Bibek (Journal of Karnali Academy of Health Sciences, 2023)
Background: This study provides information regarding severity and clinical outcome of people admitted with the diagnosis of COVID-19 infection during the global pandemic at a provincial infectious disease hospital in Gandaki Province in Nepal. The evidence from this study will be helpful to compare the clinical outcome of people admitted with COVID-19 during the outbreak.Methods: Cross-sectional study was conducted from March 2023 to August 2023 after approval from NHRC (ref. no. 1448) with sample size of 1366 at the hospital. Structured questionnaire was used to collect secondary data (electronic and paper records) retrospectively from hospital records with a diagnosis of COVID-19 infection. Total enumeration technique was used with enlisting of all cases of COVID-19 to the hospital. The collected data was analyzed using SPSS version 11.5.Results: The hospital admitted the highest number of cases between April to September 2021. Among the 1366 admitted cases, 791 (57.91%) were males and 575 (42.09%) were females, the most common age group affected was 31 to 40 years (22.99%); 1092 (79.94%) were from Kaski district. As per disease severity, 884 (64.71%) were moderate cases followed by 391 (28.62%) mild cases and 91 (6.67%) severe cases. A total of 1205 (88.21%) patients were discharged, 105(7.69%) patients were referred and 56 (4.10%) patients died of COVID - 19.Conclusions: Almost 3/4th of the admitted cases came from the same district, majority had moderate disease and the hospital cure rate was almost 8/9th.